PSYCHOLOGICAL CAPITAL DAN RESILIENSI INOVATIF SEBAGAI PREDIKTOR FLOURISHING: STUDI FENOMENOLOGI PADA PEMILIK BIRO PERJALANAN JTC - Ade Satria Kurniawan; Fx. Wahyu Widiantoro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to explore in depth the dynamics of Psychological Capital (PsyCap) and its role in fostering innovative resilience among travel agency owners in Yogyakarta affiliated with the Jogja Travel Community (JTC) ecosystem. Amidst massive tourism disruption, the strength of internal psychological capital has become a primary determinant of business sustainability. Employing a qualitative method with an Interpretative Phenomenological Analysis (IPA) design, data were gathered through in-depth semi-structured interviews with six travel agency owners. The results reveal that the HERO pillars (Hope, Efficacy, Resilience, and Optimism) work synergistically to form a creative agency, enabling participants to transform their business models from conventional to digital and niche markets. Key findings indicate that JTC serves as a